Trailer do filme Psicose, para além do marketing cinematográfico - Constantino, Maria Julia évora (2014)
The objective of this dissertation is to study the narrative of the trailer of one of the most influential films in cinema history: Alfred Hitchcock´s Psycho (1960). The trailer will, therefore, be analyzed not only as a tool of movie marketing, but mostly as a 'shortmovie' which has a kind of parallel narrative and assist in the feature film, with a beginning, middle and end, trying to understand how that is constituted and how it still speaks to the disclosure´s posters and the opening credits of the film. Both 'core' sequence storyboard´s (trailer and movie) will also be used in this reading that seeks to comprehend the process of signification in the orbit of Psycho.